Effect of Canva Based Project Based Learning on Students’ Mathematical Thinking Skills - Nur Afifah; Poppy Rachman; Athar Zaif Zairozie (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematics instruction on plane figures often remains procedural and has not optimally developed students’ mathematical thinking skills, particularly reasoning, representation, and problem solving. This condition highlights the need for instructional innovation that encourages students to engage actively in constructing meaningful mathematical concepts. This study aimed to analyze the implementation of instruction and examine the effect of Canva-assisted Project-Based Learning (PjBL) on students’ mathematical thinking skills. A quantitative approach was employed using a quasi-experimental nonequivalent control group design. The participants were 40 seventh-grade students at MTs Nurul Hasan, consisting of an experimental group and a control group, with 20 students in each group. Data were collected through pretest-posttest assessments and classroom observations, and were analyzed using t-tests, N-gain, and effect size. The results showed that the implementation of the learning process was categorized as good. A significant difference was found between the experimental and control groups (p < 0.05). The average score of the experimental group increased from 47.00 to 84.25, with an N-gain of 0.70, which was categorized as high, and an effect size of 1.81, indicating a very large effect. These findings indicate that Canva-assisted Project-Based Learning has a strong effect on students’ mathematical thinking skills. The novelty of this study lies in positioning Canva as a medium for supporting concept construction within Project-Based Learning.